Measurement of the dynamics in ski jumping using a wearable inertial sensor-based system - Chardonnens, J.; Favre,J.; Cuendet, F.; Gremion, G.; Aminian, K. (Journal of Sports Sciences, 2014)
Dynamics is a central aspect of ski jumping, particularly during take-off and stable flight. Currently, measurement systems able to measure ski jumping dynamics (e.g. 3D cameras, force plates) are complex and only available in few research centres worldwide. This study proposes a method to determine dynamics using a wearable inertial sensor-based system which can be used routinely on any ski jumping hill. The system automatically calculates characteristic dynamic parameters during take-off (position and velocity of the centre of mass perpendicular to the table, force acting on the centre of mass perpendicular to the table and somersault angular velocity) and stable flight (total aerodynamic force). Furthermore, the acceleration of the ski perpendicular to the table was quantified to characterise the skis lift at take-off. The system was tested with two groups of 11 athletes with different jump distances. The force acting on the centre of mass, acceleration of the ski perpendicular to the table, somersault angular velocity and total aerodynamic force were different between groups and correlated with the jump distances. Furthermore, all dynamic parameters were within the range of prior studies based on stationary measurement systems, except for the centre of mass mean force which was slightly lower.